2011
DOI: 10.1371/journal.pone.0025931
|View full text |Cite
|
Sign up to set email alerts
|

Population Status of a Cryptic Top Predator: An Island-Wide Assessment of Tigers in Sumatran Rainforests

Abstract: Large carnivores living in tropical rainforests are under immense pressure from the rapid conversion of their habitat. In response, millions of dollars are spent on conserving these species. However, the cost-effectiveness of such investments is poorly understood and this is largely because the requisite population estimates are difficult to achieve at appropriate spatial scales for these secretive species. Here, we apply a robust detection/non-detection sampling technique to produce the first reliable populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 16 publications
1
77
0
Order By: Relevance
“…The estimates of tiger density across our study site in Chitwan were higher than numerous sites in Central and North India (24) and several times higher than sites in Laos, Indonesia, Malaysia, and Bhutan (25)(26)(27)(28). In addition, tiger occupancy was 12-30% greater than sites in Indonesia and India (29,30). Human foot traffic across the study site was also orders of magnitude greater than traffic reported for other areas of the tigers' range (using similar methodology) (25,26).…”
Section: Discussionmentioning
confidence: 60%
“…The estimates of tiger density across our study site in Chitwan were higher than numerous sites in Central and North India (24) and several times higher than sites in Laos, Indonesia, Malaysia, and Bhutan (25)(26)(27)(28). In addition, tiger occupancy was 12-30% greater than sites in Indonesia and India (29,30). Human foot traffic across the study site was also orders of magnitude greater than traffic reported for other areas of the tigers' range (using similar methodology) (25,26).…”
Section: Discussionmentioning
confidence: 60%
“…More recently, tiger distribution studies outside of Nepal have used a relatively new approach (occupancy surveys) to assess tiger presence at the landscape scale (Linkie et al, 2006;Hines et al, 2010;Karanth et al, 2011;Wibisono et al, 2011;Sunarto et al, 2012). These studies differ from earlier research in Nepal, in part, by explicitly addressing the issue of detectability, accounting for search effort and analyzing additional covariates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…relative prey abundance and human disturbance). The utilization of occupancy methods across various tiger landscapes can also allow for more robust comparisons at regional scales (Wibisono et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…biological pollution of wild population. Briggs and Smith 10 estimated the nitrogen and phosphorus from intensively developed shrimp ponds in Thailand as it was reported that these inputs were not converted to shrimp biomass as expected, rather there was a possibility that they were released into the surrounding environment 11,12 . It may be mentioned here that in many studies the range and severity of shrimp farming impacts have been either exaggerated or misrepresented, mainly owing to the high profitability/ visibility of the aquaculture sector, failure to distinguish between actual and hypothetical hazards 13 and projection of piece meal studies which were location-specific.…”
mentioning
confidence: 97%
“…This helps in identifying source sites with high levels of certainty on tiger numbers, helping manage tiger populations in a true meta-population framework. Though attempts have been made to map occupancy of tigers at wider scales [10][11][12] , there is a need to estimate density, and absolute abundance at individual protected area scale, where reasonable logistical opportunities and resources exist. This could ultimately help in achieving global tiger recovery targets through improved coverage of scientifically assessed data.…”
mentioning
confidence: 99%